M ≥ 7 earthquake rupture forecast and time‐dependent probability for the sea of Marmara region, Turkey. Issue 4 (18th April 2016) - Murru, M.; Akinci, A.; Falcone, G.; Pucci, S.; Console, R.; Parsons, T.
Abstract: We forecast time‐independent and time‐dependent earthquake ruptures in the Marmara region of Turkey for the next 30 years using a new fault segmentation model. We also augment time‐dependent Brownian passage time (BPT) probability with static Coulomb stress changes (ΔCFF) from interacting faults. We calculate Mw  >  6.5 probability from 26 individual fault sources in the Marmara region. We also consider a multisegment rupture model that allows higher‐magnitude ruptures over some segments of the northern branch of the North Anatolian Fault Zone beneath the Marmara Sea. A total of 10 different M w  = 7.0 to M w  = 8.0 multisegment ruptures are combined with the other regional faults at rates that balance the overall moment accumulation. We use Gaussian random distributions to treat parameter uncertainties (e.g., aperiodicity, maximum expected magnitude, slip rate, and consequently mean recurrence time) of the statistical distributions associated with each fault source. We then estimate uncertainties of the 30 year probability values for the next characteristic event obtained from three different models (Poisson, BPT, and BPT + ΔCFF) using a Monte Carlo procedure. The Gerede fault segment located at the eastern end of the Marmara region shows the highest 30 year probability, with a Poisson value of 29% and a time‐dependent interaction probability of 48%. We find an aggregated 30 year Poisson probability of M  > 7.3 earthquakes at Istanbul of 35%, which increases to 47% if time dependence and stress transfer are considered. We calculate a twofold probability gain (ratio time dependent to time independent) on the southern strands of the North Anatolian Fault Zone. Key Points: Seismic rate density Time‐independent probability of earthquake occurrence Time‐dependent probability with inclusion of stress transfer